Psychological Well-Being Karyawan Studi Literatur - Maulina Amalia Sari; Ameria Monalisa (Ridwan Institute, 2021)
Psychological well-being is often referred to as psychological well-being, which is ownership of self-acceptance, control of the environment, autonomy, and positive relationships with others, has a purpose and meaning in life and has a purpose and meaning in life and has a feeling of growth and development that sustainable. In several studies, the results of the research conducted indicated that there was a significant relationship between organizational culture and psychological well-being. Then there is a significant positive relationship between gratitude and psychological well-being. Grateful people have a positive attitude towards themselves, acknowledge and accept various positive and negative aspects of themselves, and positive feelings about past lives that they have experienced. This article will use literature research as a means to discuss the effect of organizational culture and gratitude on employee psychological well-being.